2000
DOI: 10.1021/jm9905211
|View full text |Cite
|
Sign up to set email alerts
|

Acyclic Analogues of Deoxyadenosine 3‘,5‘-Bisphosphates as P2Y1 Receptor Antagonists

Abstract: P2Y(1) receptors are activated by ADP and occur on endothelial cells, smooth muscle, epithelial cells, lungs, pancreas, platelets, and in the central nervous system. With the aid of molecular modeling, we have designed nucleotide analogues that act as selective antagonists at this subtype. The present study has tested the hypothesis that acyclic modifications of the ribose ring, proven highly successful for nucleoside antiviral agents such as gancyclovir, are generalizable to P2Y receptor ligands. Specifically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0

Year Published

2000
2000
2002
2002

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(53 citation statements)
references
References 27 publications
2
51
0
Order By: Relevance
“…The involved receptor (P2Y 1 receptor), G protein (Ga11), and phospholipase C (PLC-bt) all were identi®ed, puri®ed, and cloned (Boyer et al, 1996b). This model system has been highly useful for identi®cation of P2Y 1 receptor agonists (Boyer et al, , 1996c and antagonists Camaioni et al, 1998;Kim et al, 2000). Our preliminary studies suggested high anity of MRS2279 for the P2Y 1 receptor of turkey erythrocytes .…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…The involved receptor (P2Y 1 receptor), G protein (Ga11), and phospholipase C (PLC-bt) all were identi®ed, puri®ed, and cloned (Boyer et al, 1996b). This model system has been highly useful for identi®cation of P2Y 1 receptor agonists (Boyer et al, , 1996c and antagonists Camaioni et al, 1998;Kim et al, 2000). Our preliminary studies suggested high anity of MRS2279 for the P2Y 1 receptor of turkey erythrocytes .…”
Section: Resultsmentioning
confidence: 88%
“…This receptor is relatively broadly distributed in the central nervous system and in peripheral tissues (Ralevic & Burnstock, 1998;Webb & Barnard, 1999), and its role in the platelet aggregation response to ADP has been a topic of increased interest (Leon et al, 1997(Leon et al, , 1999Jin et al, 1998;Hechler et al, 1998;Fabre et al, 1999). Our initial observation that adenosine bisphosphate molecules are competitive antagonists of the P2Y 1 receptor (Boyer et al, 1996a) has been followed by directed chemical syntheses of new molecules exhibiting potential as selective competitive antagonists of the P2Y 1 receptor Kim et al, 2000). We recently reported the synthesis of a series of ribosemodi®ed-2'-deoxyadenosine bisphosphate analogs .…”
Section: Introductionmentioning
confidence: 99%
“…2), in which the 2′-methylene has been omitted and a 2-Cl has been added (to increase affinity). MRS 2286 was an antagonist at the turkey P2Y 1 receptor with an IC 50 value of 0.84 μM, and no agonist activity was observed [21]. Furthermore, the compound was inactive at P2X 1 receptors [20].…”
Section: Ribose-modified Nucleotide Analoguesmentioning
confidence: 93%
“…Ring expansion of the ribose in the 2-Cl-N 6 -Me series (in the form of an anhydrohexitol derivative, MRS 2283, IC 50 0.566 μM) and ring contraction (in the form of a cyclobutyl derivative, MRS 2264, IC 50 0.805 μM) has further emphasized the flexibility of substitution for the ribose moiety of P2Y receptor ligands (3). An acyclic modification of the ribose ring was found to preserve affinity at the P2Y 1 receptor (20). MRS 2286 (2-[2-(2-chloro-6-methylaminopurin-9-yl)-ethyl]-propane-1,3-bisoxy(diammonium-phosphate)) was an antagonist at the turkey erythrocyte P2Y 1 receptor with an IC 50 value of 0.84 μM, and no agonist affinity was observed.…”
Section: Ribose-modified Nucleoside and Nucleotide Analogues: P2y 1 Rmentioning
confidence: 99%
“…As a result, we substituted the ribose moiety in the antagonists series with a variety of cyclic (3) (carbocylics, smaller and larger rings, conformationally constrained rings) and acyclic moieties (20), without loss of affinity for the receptor.…”
Section: Ribose-modified Nucleoside and Nucleotide Analogues: P2y 1 Rmentioning
confidence: 99%